Protagonic role of Angiotensin II in neuroendocrine response to stress (Gaceta de Ciencias Veterinarias, 2020)
The evidences indicate that both the central and peripheral Angiotensin systems coordinate the adaptive responses of the organism in the presence of stressors, under this condition the secretion of the hormone Angiotensin II is increased with the activation of its AT1 and AT2 receptors. AT1 receptors are responsible for the stress response and induce cortisol release via the hypothalamic CRH, as well as vasopressin secretion and sympathetic stimulation; with an increase in circulating catecholamines, causing an increase in pressor activity. Angiotensin II is involved in facilitating noradrenergic transmission. It has been suggested that the sympathetic response to stress requires the integrity of the Renin-Angiotensin system and the blockage of AT1 receptors affected by the hormonal and sympathetic response in the presence of stressors; these evidences indicate that Angiotensin II plays a regulatory role in individuals under stressful conditions.
Keywords: Angiotensin II; regulatory role; stress